EXTENSIVE EXPERIENCE WITH MULTIPLE LANGUAGES MAY NOT BUFFER AGAINST AGING DECLINES IN EXECUTIVE FUNCTION. (11th November 2018) - Weyman, K; Shake, M
Abstract: The question of whether bilingualism can improve aspects of cognitive function is a hotly debated topic, with evidence on both sides. A few recent studies have reported that bilingualism may provide a limited buffer against some aging-related cognitive decline. This study aimed to test that hypothesis by analyzing the combinatorial effects of age and language upon executive function (i.e., general cognitive control mechanisms that regulate cognition and behavior). Amazon Mechanical Turk was used to reach an international sample of younger (YA) and older adults (OA) from 24 countries. 81 participants were monolingual (ML: N(YA)=37, N(OA)=44), and 82 participants were bilingual/multilingual (BL: N(YA)=43, N(OA)=39). Executive function components of inhibition, updating, and switching were measured using stop signal, letter memory, and color shape tasks, respectively. ANOVAs were used to analyze the dataset. The stop signal task indicated that YA had shorter reaction times than OA, F(1, 151)=14.51, p<.001. The letter memory task showed a main effect of age in which YA recalled more letters than OA, F(1, 158)=7.65, p<.01. Finally, the color shape task revealed that a shorter cued stimulus interval led to a greater switch cost, F(1, 151)=83.87, p<.01. Notably, no effects of language (i.e., bilingualism) were significant. YA and OA performed as expected regarding normal cognitive aging; however, no interactions were found between ML and BL participants within each age group. Therefore, this study provides data that challenges the claim that extensive experience with multiple languages can be a reliably protective factor against some normative aging declines in executive function.